PERBANDINGAN PENDAPATAN PETANI PADI SAWAH PESERTA DAN BUKAN PESERTA PASAR LELANG KOMODITI AGRO (PLKA) DI KELURAHAN KINIAR KECAMATAN TONDANO TIMUR - Sisilia C. Pontoh; Juliana Mandei; Rine Kaunang; Eyverson Ruauw (Universitas Sam Ratulangi, 2014)
ABSTRACTThe objective of this research is to compare rice farmer income between participant and nonparticipant at Agro Commodity Auction Market in Kiniar, East Tondano District, Minahasa Regency.The data have been collected for four months, since September 2013 until January 2014. The data consist of Primary and Secondary data. The primary data have been earned from survey to the farmers, participant and nonparticipant directly. The secondary data have been earned from all of the institutions that related with this research.The sampling has been done by using simple random sampling technique, where 15 samples for each population were taken to find out the difference between their incomes, so that we can compare them, with t-test.The result from this research showed that the income between farmer as participant and nonparticipant at Agro Commodity Auction Market ware different. The income average of rice farmer in Kiniar as participant is higher than the income average of rice farmer as nonparticipant at Agro Commodity Auction Market.